Circulating cortisol‐associated signature of glucocorticoid‐related gene expression in subcutaneous fat of obese subjects12. (20th June 2013) - Pavlatou, Maria G.; Vickers, Kasey C.; Varma, Sudhir; Malek, Rana; Sampson, Maureen; Remaley, Alan T.; Gold, Philip W.; Skarulis, Monica C.; Kino, Tomoshige
Abstract Objective: Serum cortisol concentrations fluctuate in a circadian fashion, and glucocorticoids exert strong effects on adipose tissue and induce obesity through the glucocorticoid receptor. Design and Methods: To examine the impact of physiologic levels of circulating cortisol on subcutaneous adipose tissue, 25 overweight and obese subjects were employed, and their serum levels of morning (AM) and evening (PM) cortisol, AM/PM cortisol ratios, and 24‐h urinary‐free cortisol (UFC) were compared with their clinical parameters, serum cytokine levels, and mRNA expression of 93 receptor action‐regulating and 93 glucocorticoid‐responsive genes in abdominal subcutaneous fat. Results and Conclusions: AM cortisol levels did not correlate with mRNA expression of the all genes examined, whereas PM cortisol levels, AM/PM cortisol ratios, and 24‐h UFC were associated with distinct sets of these genes. Body mass index did not significantly correlate with the four cortisol parameters employed. These results suggest that physiologic levels of AM serum cortisol do not solely represent biological effects of circulating cortisol on the expression of glucocorticoid‐related genes in subcutaneous adipose tissue, whereas PM levels, amplitude, and net amounts of the diurnally fluctuating serum cortisol have distinct effects. Through the genes identified in this study, glucocorticoids appear to influence intermediary metabolism, energy balance, inflammation, and local circadian rythmicity in subcutaneous fat. Our results may also explain in part the development of metabolic abnormality and obesity in subjects under stress or patients with melancholic/atypical depression who demonstrate elevated levels of PM serum cortisol.